Forage production of elephant grass under intermittent stocking - Chaves, Carla Silva; Gomide, Carlos Augusto de Miranda; Ribeiro, Karina Guimarães; Paciullo, Domingos Sávio Campos; Ledo, Francisco José da Silva; Costa, Igor de Almeida; Campana, Ludmila Lacerda (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the dry matter production of elephant grass (Pennisetum purpureum) genotypes, managed under intermittent stocking. A completely randomized design was used, with two genotypes and three replicates. The treatments consisted of factorial combinations (2x2x2) of genotypes ('BRS Kurumi' and the clone CNPGL 00‑1‑3), two light interception levels (LI) at the onset of grazing (90 and 95%), and two post‑grazing canopy heights (30 and 50 cm). A total of 24 Holstein x Zebu crossbred heifers were used. The stocking density varied in order to finish the grazing periods in two days. The interval between the defoliation, based on 95% LI, resulted in a higher leaf mass per grazing cycle. The post‑grazing height of 30 cm did not affect the number of grazing cycles but provided a greater herbage accumulation rate. The cultivar BRS Kurumi has higher pasture growth, lower rest period, and greater number of grazing cycles, which results in increased forage production in the growing season.